Deployment of fuel cell vehicles in China: Greenhouse gas emission reductions from converting the heavy-duty truck fleet from diesel and natural gas to hydrogen. (17th May 2021) - Liu, Feiqi; Mauzerall, Denise L.; Zhao, Fuquan; Hao, Han
Abstract: Hydrogen fuel cells, as an energy source for heavy duty vehicles, are gaining attention as a potential carbon mitigation strategy. Here we calculate the greenhouse gas (GHG) emissions of the Chinese heavy-duty truck fleet under four hydrogen fuel cell heavy-duty truck penetration scenarios from 2020 through 2050. We introduce Aggressive, Moderate, Conservative and No Fuel Cell Vehicle (No FCV) scenarios. Under these four scenarios, the market share of heavy-duty trucks powered by fuel cells will reach 100%, 50%, 20% and 0%, respectively, in 2050. We go beyond previous studies which compared differences in GHG emissions from different hydrogen production pathways. We now combine an analysis of the carbon intensity of various hydrogen production pathways with predictions of the future hydrogen supply structure in China along with various penetration rates of heavy-duty fuel cell vehicles. We calculate the associated carbon intensity per vehicle kilometer travelled of the hydrogen used in heavy-duty trucks in each scenario, providing a practical application of our research. Our results indicate that if China relies only on fuel economy improvements, with the projected increase in vehicle miles travelled, the GHG emissions of the heavy-duty truck fleet will continue to increase and will remain almost unchanged after 2025. The Aggressive, Moderate and Conservative FCV Scenarios will achieve 63%, 30% and 12% reductions, respectively, in GHG emissions in 2050 from the heavy duty truck fleet compared to the No FCV Scenario. Additional reductions are possible if the current source of hydrogen from fossil fuels was displaced with increased use of hydrogen from water electrolysis using non-fossil generated electricity. Highlights: Heavy-duty truck (HDT) fleet GHG emissions in China are calculated for various fuel cell scenarios. Improvements in HDT fuel economy will be offset by increased total miles travelled. Increasing penetration of HDTs powered with hydrogen can effectively reduce fleet GHG emissions. Moving towards non-fossil electrolysis of water as a source of hydrogen is critical.